(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Employee retention refers to the ability of an organization to retain its employees. Each research investigation is expected to make a definitive contribution to the existing literature. Management has always had a hard time with employees who quit on their own. In recent years, the high demand for skilled employees and the growth of service industries have led to a huge turnover rate, which affects the employer, and in the end the organization’s productivity and profitability. Present study was the employees of the IT sector; especially software engineers of various IT companies in Chennai city. Respondents were selected randomly. Employees were mainly from TCS, TechMahindra, Honeywell, Caterpillar, IBM. The information of this research will be useful to service industry in their HR practices and add new information to literature. It will help the management of the IT Sector to develop their new strategies of retention. The study found the influence of HR policies, compensation and benefits, work pressure and relationship with the superiors on employee retention.